2008
DOI: 10.1111/j.1600-0420.2007.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab (Avastin®) in proliferative diabetic retinopathy

Abstract: . Purpose:  To evaluate the efficacy and safety of intravitreal bevacizumab in proliferative diabetic retinopathy (PDR) patients. Methods:  This interventional case series study included 15 eyes of 10 patients with bilateral PDR: 13 eyes with severe PDR and active new vessels (NV) and two eyes with recurrent vitreous haemorrhages. Study eyes received a single intravitreal injection of 1.25 mg (0.05 ml) bevacizumab. All eyes were followed up for 3 months, and eight of them for 9 months. Reinjection was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 21 publications
0
41
1
1
Order By: Relevance
“…Minnella et al 40 reported that the early effects of bevacizumab were maintained at 3 months in 15 injected eyes. Likewise, Schmidinger et al 41 reported that 62% (8 of 13) of eyes required retreatment with bevacizumab at a 3-month follow-up visit because of the reappearance of new vessels.…”
Section: Methodsmentioning
confidence: 99%
“…Minnella et al 40 reported that the early effects of bevacizumab were maintained at 3 months in 15 injected eyes. Likewise, Schmidinger et al 41 reported that 62% (8 of 13) of eyes required retreatment with bevacizumab at a 3-month follow-up visit because of the reappearance of new vessels.…”
Section: Methodsmentioning
confidence: 99%
“…5 Previous reports on the intravitreal injection of bevacizumab showed promise in targeting VEGF-implicated intraocular neovascularization that is associated with age-related macular degeneration and diabetic retinopathy. [6][7][8][9][10] Recently, intravitreal bevacizumab injection has also gained popularity among vitreo-retinal surgeons as an adjunct to vitrectomy in the management of severe PDR. [11][12][13] Other growth factors and cytokines including angiopoietin-2, 14 insulin-like growth factor-1, 15 erythropoietin, 16 hypoxia-inducible factor, 17 platelet-derived growth factor, 18 fibroblast growth factor-2 19 and hepatocyte growth factor 20 have also been demonstrated to be involved in ocular angiogenesis.…”
Section: )mentioning
confidence: 99%
“…It has been shown to reduce neovascular activity and vascular permeability in ocular tissues. 4,5 Nevertheless, despite the overexpression of VEGF in uveal melanoma, 2 at present no anti-angiogenic drug has been shown to clinically suppress tumour growth. 6 Currently, standard therapies include enucleation, local resection or radiotherapy, either by proton beam irradiation, stereotactic or brachytherapy (iodine or ruthenium).…”
Section: Treatment Of Primary Tumourmentioning
confidence: 99%